Semi Strong Form Efficiency Test of the Nigerian Stock Market: Evidence from Event Study Analysis of Bonus Issues - Manasseh, Charles O.; Ozuzu, Chukwuka Kenneth; Ogbuabor, Jonathan E. (International Journal of Economics and Financial Issues, 2016)
This study tests the consistency of the Nigerian Stock Market with the Efficient Market Hypothesis (EMH) in the semi-strong form using bonus issues as the information generating event. Using daily data, a total of 121 bonus issues were observed and examined for the period 2002-2006. The stocks which were tested were classified according to the size of their bonus issues and also according to the price of the stock to know the impact of information released on the price of different categories of stock. Using the event study methodology, the market and the market adjusted models as well as the VAR models, the study discovered that information release impacts significantly only in the year 2002. Also, it reveals that small bonus issues responded speedily to bonus issues more than medium and large bonus issues. In addition, the test between penny stocks and blue chips shows that only penny stocks were significantly affected. Keywords: Semi-Strong Form, Efficiency, Stock Market, Event Study, Bonus Issues JEL Classifications: G10; G11; G12; G14